Allometric Models for Estimating Tree Volume and Aboveground Biomass in Lowland Forests of Tanzania. (14th January 2016) - Mugasha, Wilson Ancelm; Mwakalukwa, Ezekiel Edward; Luoga, Emannuel; Malimbwi, Rogers Ernest; Zahabu, Eliakimu; Silayo, Dos Santos; Sola, Gael; Crete, Philippe; Henry, Matieu; Kashindye, Almas
Abstract : Models to assist management of lowland forests in Tanzania are in most cases lacking. Using a sample of 60 trees which were destructively harvested from both dry and wet lowland forests of Dindili in Morogoro Region (30 trees) and Rondo in Lindi Region (30 trees), respectively, this study developed site specific and general models for estimating total tree volume and aboveground biomass. Specifically the study developed (i) height-diameter (ht-dbh) models for trees found in the two sites, (ii) total, merchantable, and branches volume models, and (iii) total and sectional aboveground biomass models of trees found in the two study sites. The findings show that site specific ht-dbh model appears to be suitable in estimating tree height since the tree allometry was found to differ significantly between studied forests. The developed general volume models yielded unbiased mean prediction error and hence can adequately be applied to estimate tree volume in dry and wet lowland forests in Tanzania. General aboveground biomass model appears to yield biased estimates; hence, it is not suitable when accurate results are required. In this case, site specific biomass allometric models are recommended. Biomass allometric models which include basic wood density are highly recommended for improved estimates accuracy when such information is available.